Pengaruh Motivasi Kerja dan Kecerdasan Emosional Terhadap Kinerja Guru di MTsS Maghfirah Islamic Leadership Boarding School (MILBoS) - Akbar; Annisa Hafsah Azzahra; Nurlia Azzahra (ISEDU : Islamic Education Journal, 2026)
Education plays a vital role in improving quality of life and societal progress, with teachers serving as educators, motivators, and facilitators. This study aims to analyze the effect of work motivation and emotional intelligence on teacher performance at MTsS MILBoS. A quantitative approach with an ex-post facto design was applied to 32 teachers selected through the Slovin formula and simple random sampling. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression with SPSS, preceded by validity, reliability, and classical-assumption tests. The results show that, in separate simple regressions, work motivation accounted for 31.1% and emotional intelligence for 68.3% of the variance in teacher performance; in the combined multiple regression model, both variables simultaneously explained 74.5% (F = 42.458; p < 0.05), while the remaining 25.5% was attributable to other factors. Both variables exerted a positive and significant partial effect, with emotional intelligence the stronger predictor. The study concludes that strengthening work motivation and emotional intelligence improves teacher performance; institutions are therefore advised to provide rewards, training, and a conducive work environment. Future research may incorporate additional variables for broader explanatory power.